Pembingkaian Isu Pembangunan Destinasi Wisata Premium Komodo Melalui Media Sosial Twitter - Ben Isa Muhammad (MEDIALOG: Jurnal Ilmu Komunikasi, 2021)
The issue of the development of the komodo premium tourist destination went viral because of a tweet on a social media, twitter. The tweet posted a photo of a Komodo dragon and a truck facing each other and there was a narrative questioning the sustainability of the Komodo ecosystem. These photos and narratives were then retweeted and mentioned by various other accounts and the hashtag #savekomodo appeared so that it became a trending topic and went viral. Twitter is a social media medium commonly used by Indonesian people to discuss various topics. Such topics can be framed based on perceptions and even certain account interests. This study uses a qualitative approach with framing analysis method Gamson-Modigliani model to examine how the viewpoints presented by four Twitter account posts frame the development issue of the Komodo National Park. More. The results of the study concluded that the first tweet on twitter actually attracted a response from the audience, who then reacted to the tweet while still carrying the initial tweet. The first tweet becomes the main frame which is then amplified by various reactive tweets that add a new layer of framing. The framing process grows organicly based on the audiences response on the social media network, but still carries the originall message (framing)